The Death of Jesus in Mark and the Miracle from the Cross - Jackson, Howard M. (New Testament studies, 1987)
At the primary, narrative level the riddle of Mark's brief account of Jesus' death and its immediate aftermath must still be pronounced unsolved. There has been a steadily growing awareness among scholars that, for all the insights they have afforded us, form and redaction criticism have tended to deprive the Evangelists of reputations for competence as narrators and their story-lines of coherence and integrity and that this tendency does them injustice. Yet though the latest study of Mark 15. 37–39 is sensitive to this issue, it cannot be pronounced successful in making complete sense of Mark's narrative qua narrative. This paper offers a solution to the riddle and argues what I realize is the rather radical thesis that Mark intended a connection between the events of these verses that has never been fully and properly understood.